KEBIJAKAN PENDIDIKAN BAHASA INDONESIA DALAM PERSPEKTIF PENDIDIKAN NASIONAL - Siti Rochmiyati (Universitas Sarjanawiyata Tamansiswa, 2015)
The aims of National Education (Pendidikan Nasional) is to educate the whole of the nation in accordance with comprehensive manners such as spiritual intelligence, intellectual intelligence, and kinesthetic intelligence. Those kinds of Indonesian intelligence embodied by home’s education, school’s education, and society’s education or Three Center of Education (Tripusat Pendidikan). The policy is an action guide that tends to individual or institutional. Therefore, the linguistic education policy should be defined in comprehensive and futuristic ways. Indonesian Language Learning as one of lesson core requires the teacher to apply a learning strategy that motivates student to use language as a media to think and deliver their intelligence in a correct and well behaved, and also characterless. The Indonesian Language can be a carrier of knowledge and student basic structure of thinking with an optimal function apply of language.